Raising the Quality of Child Caregiving in Bangladesh - Rahman, Tashmina; Arnold, Tamara; Shams, Farzana; Rahman, Mokhlesur (World Bank, Washington, DC, 2022)
Access to quality childcare is critical for improving child development outcomes and ensuring that the next generation of Bangladeshi children are better prepared to contribute as active citizens. Child caregivers play a pivotal role in developing children’s physical and cognitive growth in the early years of life. Moreover, access to quality childcare has been linked to higher women’s labor force participation and better economic growth. However, there remains a knowledge gap in the area of child caregiver skills, globally and particularly in the case of Bangladesh. In the case of Bangladesh, there is critical need to understand the complex child caregiver training structure and means to improve the system in helping the country ensure better child development outcomes, higher female workforce participation and ultimately its goal of becoming a developed country in the next two decades. This study uses a mixed method approach to - first, understand the current status of child caregivers and childcare services in Bangladesh and second, assess the current training programs available and opportunities for professional development for the childcare workforce. The study investigates the socio-economic profiles; training acquired and perceptions of skills gaps and the environment in which child caregivers and center managers operate across different types of providers. The key recommendations emerging from the study are then discussed along four areas: polices, quality caregivers, pedagogical approach and enabling environment.